2014
DOI: 10.1177/0960327114521049
|View full text |Cite
|
Sign up to set email alerts
|

The role of S100B protein, neuron-specific enolase, and glial fibrillary acidic protein in the evaluation of hypoxic brain injury in acute carbon monoxide poisoning

Abstract: The main purpose of this study was to assess the role of S100B protein, neuron-specific enolase (NSE), and glial fibrillary acidic protein (GFAP) in the evaluation of hypoxic brain injury in acute carbon monoxide (CO)-poisoned patients. This cross-sectional study was conducted among the patients with acute CO poisoning who referred to the emergency department in a 1-year period. Serum levels of S100B protein, NSE, and GFAP were determined on admission. A total of 55 CO-poisoned patients (mean age ± st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…5,6 While the COHb level is easily and rapidly available at most institutions other biomarkers having been proposed to serve as better predictors of severity and prognosis in CO poisoning that include lactate and S100B but have yielded variable results. 7,8 The presence of microparticles in blood is also currently being explored as a potential biomarker for CO poisoning. 9 Many of these markers act as secondary measures of CO poisoning but do not directly measure the effects of CO.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 While the COHb level is easily and rapidly available at most institutions other biomarkers having been proposed to serve as better predictors of severity and prognosis in CO poisoning that include lactate and S100B but have yielded variable results. 7,8 The presence of microparticles in blood is also currently being explored as a potential biomarker for CO poisoning. 9 Many of these markers act as secondary measures of CO poisoning but do not directly measure the effects of CO.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported an association between increased serum NSE levels or cerebrospinal fluid (CSF) NSE levels and central nervous system (CNS) damage and neurological diseases [acute ischemic stroke , traumatic brain injury , Alzheimer's disease , delirium and epileptic seizures ]. In addition to cerebral injury, increased serum NSE levels have also been found to be associated with essential hypertension , lung cancer , acute carbon monoxide poisoning , pediatric cancer , renal cell carcinoma , diabetic peripheral neuropathy , and multiple myeloma .…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Akdemir, where the roles of S100B, NSE, and GFAP in the assessment of hypoxic cerebral injury among patients with acute CO poisoning, S100B, NSE and GFAP's serum levels were significantly higher in the patient group than in the control group. 4 Akelma et al could not find any correlation between S100B protein level and Glasgow Coma Score (GCS) in children with CO poisoning. They detected that S100B protein level did not increase but NSE level increased.…”
Section: Discussionmentioning
confidence: 97%
“…Non-COHb biochemical markers have been investigated to predict CO poisoning, which is particularly neurotoxic and cardiotoxic. [3][4][5][6] Dogan et al reported that COHb levels are positively correlated with lactate levels in CO intoxication. 7 Netrins are important precursor proteins for neural and vascular development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation